2021
DOI: 10.1002/cpdd.903
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Concentration‐QTc and Cardiac Safety Analysis of the MDM2 Antagonist KRT‐232 in Patients With Advanced Solid Tumors, Multiple Myeloma, or Acute Myeloid Leukemia

Abstract: Cardiac safety and plasma concentration-QTc interval analyses were completed using data from 2 phase 1 studies of the selective mouse double minute chromosome 2 antagonist, KRT-232, in patients with solid tumors or multiple myeloma and acute myeloid leukemia (AML) who received KRT-232 doses of 15 to 480 mg once daily (QD; N = 130). A linear mixed-effects model related change from baseline Fridericia-corrected QT interval (QTcF) to KRT-232 plasma concentrations. The final model included parameters for the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Another study[ 30 ] showed that 2/10 patients required hospitalization and 3/10 developed an encephalopathy episode after FMT at 20 wk. FMT also appeared to be safe and well tolerated[ 31 ].…”
Section: Gut Flora Modifying Agentsmentioning
confidence: 99%
“…Another study[ 30 ] showed that 2/10 patients required hospitalization and 3/10 developed an encephalopathy episode after FMT at 20 wk. FMT also appeared to be safe and well tolerated[ 31 ].…”
Section: Gut Flora Modifying Agentsmentioning
confidence: 99%
“…Navtemadlin is now being evaluated in the treatment of a variety of malignancies, including leukemia, myeloproliferative neoplasms, myeloma, sarcoma, lung cancer, and brain cancer, both as a single agent and as a part of combination regimens. Erba et al (2019) previously reported an LC-tandem mass spectrometry (LC-MS/MS) bioanalytical method for the pharmacokinetic analysis of navtemadlin in NCT02016729; this method has subsequently been used in other clinical studies (Gluck et al, 2020;Taylor et al, 2021). However, these prior studies lack sufficient details of the bioanalytical method, including but not limited to sample preparation, chromatography, and stability information, and they have also not validated the method using brain tissue.…”
Section: Navtemadlin (Previously Krt232 and Amg232mentioning
confidence: 99%
“…Navtemadlin is a small‐molecule, highly protein‐bound (97.5%) monoprotic carboxylic acid (pK a 4.35) that is primarily metabolized to a major circulating acyl glucuronide metabolite (M1) 17 . The structure of navtemadlin and M1 have been previously published 17–19 . In previous studies, M1 has been shown to be stable in vitro and demonstrated 5‐fold less pharmacologic activity than the parent drug in a biochemical homogeneous time‐resolved fluorescence in vitro pharmacologic potency assay in the presence of 15% serum and was highly bound to plasma proteins 19 .…”
mentioning
confidence: 99%
“… 17 The structure of navtemadlin and M1 have been previously published. 17 , 18 , 19 In previous studies, M1 has been shown to be stable in vitro and demonstrated 5‐fold less pharmacologic activity than the parent drug in a biochemical homogeneous time‐resolved fluorescence in vitro pharmacologic potency assay in the presence of 15% serum and was highly bound to plasma proteins. 19 In patients with solid tumors or multiple myeloma, the mean time to maximum concentration (t max ) of the metabolite M1 was 2 to 4‐hours, and the mean (standard deviation [SD]) terminal half‐life (t 1/2 ) was 14.0 (6.07) hours.…”
mentioning
confidence: 99%
See 1 more Smart Citation